2009
DOI: 10.1007/s10815-009-9312-z
|View full text |Cite
|
Sign up to set email alerts
|

Follicular and luteal phase endometrial thickness and echogenic pattern and pregnancy outcome in oocyte donation cycles

Abstract: Purpose To study the effect of endometrial thickness (ET) and echogenic pattern (EP) in oocyte donation cycles upon pregnancy outcomes. Methods Seventy-nine cycles resulting in blastocyst embryo transfer were evaluated. Donors underwent ovarian hyperstimulation using rFSH and GnRH-antagonist. Recipients were synchronized to donors using GnRH-agonist downregulation followed by fixed dose of estrogen (E2) and progesterone (P4) following hCG. Transvaginal ultrasound (US) obtained ET and EP 10-11 days after initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 31 publications
7
48
1
Order By: Relevance
“…Thus, our findings would be an underestimate of the true association between endometrial thickness and IVF success. Finally, our study does not address the relationship of endometrial thickness in donor cycles or subsequent thaw cycles, though there are some data to suggest that endometrial thickness may play less of a role in pregnancy outcomes of donor cycles (Barker, Boehnlein, Kovacs, & Lindheim, 2009; Dain et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our findings would be an underestimate of the true association between endometrial thickness and IVF success. Finally, our study does not address the relationship of endometrial thickness in donor cycles or subsequent thaw cycles, though there are some data to suggest that endometrial thickness may play less of a role in pregnancy outcomes of donor cycles (Barker, Boehnlein, Kovacs, & Lindheim, 2009; Dain et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…We were able to maintain a large sample size while using only first cycles, which eliminated the need to account for repeated measures. Many prior reports used multiple cycles per woman, and in several it appears that the investigators did not account for the correlation among these cycles (Barker et al, 2009; Chen et al, 2010; Dain et al, 2013; Kovacs, Matyas, Boda, & Kaali, 2003; Weissman et al, 1999). An additional strength of this study is that our database has undergone multiple iterations of verification for data accuracy and completeness, leading to a robust dataset with high fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial pattern was defined as the type of relative echogenicity of the endometrium compared with adjacent myometrium (24). A multilayered endometrium, appearing as a triple-line pattern, was defined as grade A.…”
Section: Recipientsmentioning
confidence: 99%
“…48 Endometrial pattern and thickness were not predictive of pregnancy outcomes in oocyte donation cycles, both prior and following progesterone administration. 49 However, in frozen embryo transfers, it was showed that an increase in progesterone dosage when there is not a mid luteal nonhomogeneous pattern could lead an increased pregnancy rate. 50…”
Section: Dsjuogmentioning
confidence: 99%